2007
DOI: 10.1056/nejmoa065497
|View full text |Cite
|
Sign up to set email alerts
|

Case–Control Study of Human Papillomavirus and Oropharyngeal Cancer

Abstract: Oral HPV infection is strongly associated with oropharyngeal cancer among subjects with or without the established risk factors of tobacco and alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

78
1,945
10
81

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,376 publications
(2,114 citation statements)
references
References 36 publications
78
1,945
10
81
Order By: Relevance
“…Part of the reasons behind this phenomenon is the increased incidence of high risk human papillomavirus (HPV) related OPSCC [1][2][3]. Interestingly, multiple retrospective studies have shown that patients with HPVpositive OPSCC have a better prognosis compared to patients with HPV-negative tumors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Part of the reasons behind this phenomenon is the increased incidence of high risk human papillomavirus (HPV) related OPSCC [1][2][3]. Interestingly, multiple retrospective studies have shown that patients with HPVpositive OPSCC have a better prognosis compared to patients with HPV-negative tumors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Oral cancer significantly impacts quality of life, physically and psychosocially, and the genetic links between some types of oral-pharyngeal carcinomas and ano-genital malignancies have been established via the human papillomavirus (HPV), particularly the strains 16 and 18 as found by Herrero et al (2003) and others (Anhang, Goodman, & Goldie, 2004;Cox, 2000;D'Souza et al, 2007;Ha & Califano, 2004). Since HPV 16 is the most predominant strain in ano-genital carcinomas, its transmission to the oropharyngeal region can occur through the mouth, especially during oral sex in sexually active individuals (Scully, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, two of the high-risk HPV types, HPV16 and 18, are responsible for approximately 70% of cervical cancer and are also the HPV types most often found in HPV-associated cancers at other sites. A lower percentage of several additional cancers can be associated with persisting high-risk HPV infection, including cancers of anogenital epithelium (vulval, vaginal, penile, anal), with HPV-attributable fractions between 40-90%, and some cancers of other mucosal epithelial surfaces [11]. Most HPV infections are asymptomatic and resolve spontaneously with a median time to resolution of less than 1 year [12].…”
Section: Human Papillomaviruses (Hpv)mentioning
confidence: 99%